Penggunaan Geogebra Untuk Meningkatkan Pemahaman Relasi dan Fungsi Siswa Kelas VIII SMP - Putrinanda, Marcia; Mairing, Jackson Pasini; Sugiharto, Sugiharto (Journal Of Dehasen Educational Review, 2025)
This study aims to describe the effectiveness of using Geogebra in improving students’ understanding of relations and functions as well as their learning activities, while also describing the implementation process and obstacles experienced by students during the learning. This learning was designed with a Deep Learning approach contained in Geogebra-based student worksheet (LKPD). This study uses a mixed-methods approach with a sequential explanatory design. The research subject consisted of 25 eight-grade students at Bethel Palangka Raya Junior High School. Quantitative data were collected through pretest, posttest, and questionnaires, while qualitative data were obtained through interviews and students’ work on the worksheets (LKPD). The result showed a significant increase in the N-Gain score of 0,47 (medium category). Statistical tests also showed significant difference in understanding before and after using Geogebra (sig. = 0.008). The results of the positive response were also obtained through questionnaires and interview with three students.